The Enigma of the Temple Site and the Word-play ‘Moriah’ - Martin Prudký (Teologická Reflexe)
The name ‘Moriah’ is conventionally associated with the Temple Mount in Jerusalem. In Jewish tradition, this identification is attested in a number of texts, including one biblical reference (2 Chr 3:1). On the other hand, other biblical passages where we might expect such an identification do not contain the name ‘Moriah’ nor a precise localization. This study examines the enigmatic name ‘Moriah’, which in the narrative of the patriarch Abraham (Gen 22:1–19) – one of Israel’s primary foundation narratives – describes the sacrificial cult site without precisely locating it. This name is nowhere attested as a primary toponym. Its form is actually a common noun that generates significant semantic allusions to and connotations with several key motifs of the narrative in question. Hence, the term ‘Moriah’ is a skillful wordplay, a pun using allusions and imagination in the given literary context of the Abrahamic cycle. As part of the foundation narratives shared by the two ‘ecumenical’ communities of post-exilic Judaism, the name helps to etiologically legitimize the place of worship (‘ha-maqom’, the temple) for both the Jerusalemite and Samaritan cultic communities without using real names and locations. The shared Torah text is open to both perspectives of reading and to both identifications that we find in the history of reception.